EVALUATION OF ANTIDEPRESSANT ACTIVITY OF CYMBOPOGONCITRATUS EXTRACTS IN MICE - MAGOTRA, SUMEET; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2025)
Objective: To evaluate Antidepressant Activity of Aqueous and Ethanolic extracts of Cymbopogoncitratus in albino mice by using Forced swimming test (FST) and Tail suspension test (TST) parameters. Methods: Healthy, adult Swiss albino mice of either sex weighing (25-40 g), maintained under standard laboratory conditions at temperature 25±2 °C and a 12 h light-12 h dark period will be employed for the experimentation. Food and water will be provided ad libitum. Antidepressant Animal model A) Forced swimming test: In this model, the animal is placed in a glass cylinder (30 cm in diameter and 50-cm height) containing 40 cm of water at 23±1 °C for 5 min, forcing the mice to either swim or float. b) Tail suspension test in mice: In this model, five animals are treated with test compounds or a vehicle via injection 30 min before being suspended by their tails. Immobility is recorded for 5 min, with the mouse considered immobile after hanging motionless for 1 min. A low-dose study found no effect of cymbopogoncitratus (lemongrass) oil on humans. However, higher doses enhance GABA-ergic transmission, like benzodiazepines, used for anxiety and sedation. To reduce anxiety, an adult would need 600–800 mg of pure oil, while most supplements contain lower doses, likely relying on the placebo effect. It may also synergize with other anxiolytics. Results: In the present study, we have undertaken the antidepressant activity of ethanolic and aqueous extracts of Cymbopogoncitratus in Swiss albino mice at the dose of 250 and 500 mg/kg with oral administration, respectively. Conclusion: In conclusion, both the extracts ethanolic and aqueous extracts of Cymbopogoncitratus have shown significant results as an antidepressant effect using forced swim test (FST) and Tail Suspension test (TST) parameters.